Nienawiść realna czy wymyślona ? Relacje między Grekami a Kartagińczykami na Sycylii w czasach Dionizjusza I - Andrzej Dudziński (In Gremium. Studies in History, Culture and Politics, 2017)
Hatred real or invented? Relations between the Greeks and the Carthaginians in SicilLy in times of Dionysius IThe article addresses the issue of relations between the Greeks and the Carthaginians in Sicily 410- 67 BC. The aim of the article is to reach beyond the open statements of general hostility, present in the literary sources, and to focus on the events described by said sources. First, the anaysis focuses on the seemingly abundant evidence of fear and hate between the Greeks and the Carthaginians. The closer study, however, suggests that most of these instances are closely connected with either bjectivethreats (e.g. war), or the actions of Dionysius I, tyrant of Syracuse, who repeatedly used the fear of the Carthaginians, at first as a measure to reach for power, and later to keep it. Thus, there is little solid evidence for any negative feelings between the two peoples. Conversly, the analysis of the events on the island provide some evidence for positive relations between the Greeks and the Phoenicians in Sicily. The examples of cohabitation, migrations, personal relationships and, above all, normal diplomatic relations paint a picture very different to the open declarations of the sources. Therefore, it is suggested that there was no significant animosity between the Greeks and the Phoenicians and that it was Dionysius’ propaganda that framed the conflict into the panhellenic (or pansiceliote) context.